2016
DOI: 10.1080/13102818.2016.1175966
|View full text |Cite
|
Sign up to set email alerts
|

Chronic toxoplasmosis and possible risk factors associated with pregnant women in Khyber Pakhtunkhwa

Abstract: Toxoplasmosis is the major cause of abortion and stillbirths among women of childbearing age. The aim of this study is to determine chronic Toxoplasma gondii infection at various trimesters of pregnancy and to identify various possible routes of transmission and contamination in North-West Pakistan. A total of 733 blood samples were randomly obtained from antenatal/maternity centres. A detail questionnaire was designed to analyse the clinical history of the subjects tested for specific anti-Toxoplasma IgG anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 14 publications
7
17
1
2
Order By: Relevance
“…The highest T.gondii antibodies were found 213 (43.2%) in those pregnant women in the third trimester and there was a statistically significant association between the gestational age at (first, second and third trimester) and seropositivity of T.gondii antibody. This result is in agreement with other studies reported from Ethiopia [17] and Saud Arabia [33] but different reports from this finding were reported from Ethiopia [18, 31], Rwanda [30] and Egypt [37]. In this study 168(53.9%) of the participants had at least elementary education however, no significant difference was observed between the different levels of education.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The highest T.gondii antibodies were found 213 (43.2%) in those pregnant women in the third trimester and there was a statistically significant association between the gestational age at (first, second and third trimester) and seropositivity of T.gondii antibody. This result is in agreement with other studies reported from Ethiopia [17] and Saud Arabia [33] but different reports from this finding were reported from Ethiopia [18, 31], Rwanda [30] and Egypt [37]. In this study 168(53.9%) of the participants had at least elementary education however, no significant difference was observed between the different levels of education.…”
Section: Discussionsupporting
confidence: 91%
“…Drinking of unpasteurized milk was significantly associated with seropositivity of T. gondii (OR = 0.871, 95% CI, 1.531–2.221, P = 0.033). Consistent results were reported from London [7], Khyber [33] and Egypt [37]. Inconsistent results in this study were reported from Ethiopia [16, 32], Cameroon [36] and Burkina Faso [43].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is reported that about 50% of all human T. gondii infections are foodborne [13], and 30-63% of infections are associated with the consumption of meat [1]. Some recent reports from Pakistan showed the prevalence of T. gondii in human population range from 12-28% [14][15][16]. This study was, therefore, designed to analyze T. gondii in blood and tissues of domesticated and broiler chickens and to associate it with the prevalence of infection in human beings in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the highest occurrence was found in those women who had contact with cats and the occurrence of T. gondii was found statistically significant ( P < 0.05). Our results are consistent with previous results (Majid et al ., 2016). They found a strong and significant relationship among the pregnant women in Khyber Pakhtunkhwa, Pakistan and the disease incidence ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%